A case of carbidopa/levodopa associated colitis mimicking inflammatory bowel disease - Michael J. Steel; James Conner; Sandra Nelles; Richard Kirsch (Elsevier, 2022)
Carbidopa/levodopa is widely used in the management of Parkinson's disease. We report a 77-year-old male with Parkinson's disease who developed severe, protracted pancolitis and ileitis after 5-months of treatment with carbidopa/levodopa. The clinical presentation and endoscopic findings initially resembled acute infectious colitis and later inflammatory bowel disease. The patient was unresponsive to intravenous corticosteroids and biologic therapy. Biopsies showed severe colitis with some features suggesting a drug effect (e.g. prominent crypt apoptoses, attenuated and regenerating crypts, and crypt dropout). Discontinuation of carbidopa/levodopa was associated with clinical and endoscopic resolution of the colitis. Levodopa, in combination with benserazide was later re-introduced, without a recurrence of the patient's gastrointestinal symptoms. We therefore propose carbidopa as the likely cause of colitis in this case.